Investigating and Completing Khanlari’s Theory on Metrical Units - Abbas Jahed Jah (Literary Arts)
Metrical units have a special place in the study of prosody, and as such, scholars have always paid particular attention to their scansion and naming. Parviz Natel Khanlari was one of the first to address the topic of metrical units in modern Persian prosody. Khanlari proposed ten metrical units—four of which are disyllabic and six trisyllabic—to describe the meter of Persian poetry. Despite the innovation of this new approach in prosody, some weaknesses prevented it from gaining acceptance among scholars. This research critically evaluates Khanlari’s method of structuring metrical units, aiming to identify its strengths and weaknesses. Additionally, by addressing these weaknesses and improving the theory, it seeks to enhance the effectiveness of this method. This study demonstrates that by completing and refining Khanlari’s approach, it is capable of describing Persian poetic meter, providing a novel understanding of the nature of metrical patterns, and can aid in simplifying the teaching of prosody while deepening its comprehension. For the first time, in this study, Khanlari’s units are practically applied, and the following proposals are made to complete his theory: organizing scansion based on repetition and alternation while avoiding irregular patterns, showing repetitions and alternations larger than three syllables; adding a unit to Khanlari’s six trisyllabic units; using a shortened monosyllabic unit and explaining the naming of shortened units. Keywords: Persian Prosody, Metrical Units, Parviz Natel Khanlari. Introduction Metrical units are crucial in the musical structure of poetry, and therefore, scanning the meter into units and naming them has always been a critical part of the study of prosody. Khanlari is one of the scholars who has made significant efforts to address the challenges of traditional prosody. One of the issues Khanlari tackled was the segmentation of meters into units and consequently the naming of these metrical units. While his proposal, like many of his other ideas, faced criticism, what is common in these critiques is the focus on the weaknesses of Khanlari’s method. Critiques emphasizing its positive aspects and aiming for improvement are largely absent. Two critiques stand out in the analysis of Khanlari’s segmentation and naming method: those by Najafi (2015) and Ghahramani Moghbel (2010). Khanlari’s suggested method was never fully applied by him or others, thus leaving it shrouded in ambiguity, which necessitates a practical evaluation of its strengths and weaknesses.The research pursues two primary objectives: first, to precisely describe Khanlari’s metrical units and identify the advantages and weaknesses of this type of segmentation; second, to refine, complete, and apply this method in alignment with later advancements and findings in prosody since Khanlari’s time. Materials and Methods The scope of this research is Khanlari’s theory on metrical units as discussed in the book The Meter of Persian Poetry (Khanlari, 1994). This research is conducted based on qualitative data, evaluating Khanlari’s theory through a descriptive-analytical approach. Following the identification of the theory’s strengths and weaknesses, attempts are made to refine and improve the theory consistent with new prosodical findings, with its utility evaluated post-amendments. Addressing critiques of Khanlari’s work and solving the issues raised, alongside assessing the application of Khanlari’s method in scanning and naming meters, are the main approaches used to achieve the outcomes of this research. Research FindingsAdvantages of Khanlari’s MethodSimplicity: The greatest merit of Khanlari’s method lies in its simplicity. A set of ten metrical units (eleven after completion) suffices to name all Persian meters.Offering a Unique and Sometimes More Accurate Understanding of Meter’s Nature: Khanlari’s method has the capability to reveal alternations in meters apparently formed solely from repetitive units, and similarly, to highlight repetitions in meters seemingly established by alternation alone.Educational Benefits: When placed alongside traditional metrical units, it better highlights the conventional nature of metrical units and opens the way for a deeper understanding of the formation of meters.Emphasis on the Difference between Persian and Arabic Prosody: It is now known that the meters of Persian and Arabic poetry, despite some commonalities, are distinctly separate systems. Utilizing Khanlari’s units can put an end to the misconception of equating Persian and Arabic poetic meters.Practical Problems of Khanlari’s TheoryWeakness in Demonstrating Large Metrical Structures: Khanlari’s focus on disyllabic and trisyllabic units optimizes his method for describing small metrical structures, but it lessens its power in describing larger structures.Absence of a Monosyllabic Unit: In Khanlari’s prosody, there is no monosyllabic unit. Therefore, when Khanlari encounters a monosyllabic unit at the end of a meter, he experiences confusion and difficulty.Incomplete Set of Trisyllabic Units: Khanlari’s prosody contains six trisyllabic units, which is insufficient for representing all trisyllabic units in Persian prosody, missing a unit with the syllable pattern of two longs and one short (- - U). Discussion of Results and Conclusions Completing Khanlari’s Theory and Addressing Its FlawsAdding a Marker: By adding a marker to indicate repetitions and alternations larger than three syllables (four and five syllables), the weakness in this theory in illustrating these structures can be resolved. The use of a comma is suggested, as it marks the boundary between units in pronunciation as well as in writing. This way, what lies between two pauses serves as a counterpart to the units in other segmentation methods. For example, the two units “Chame” and “Ava” in Khanlari’s prosody are equivalent to the “fa‘elatun” unit. By placing commas before and after these two units, “Chame Ava” is equated to “fe‘elatun” and will have its functionality.Shortened Units: The monosyllabic unit in Khanlari’s prosody only appears at the end of hemistiches and is always considered a shortened unit. Khanlari does not formally recognize it. To resolve this issue, the monosyllabic unit at the end of verses should be independently acknowledged.Adding a Trisyllabic Unit: A trisyllabic unit with the syllable pattern (- - U) is missing from Khanlari’s units. To address this, the unit “Avaze” is introduced following Khanlari’s naming convention.